2022
DOI: 10.34133/2022/9814652
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the LSD1-G9a-ER Stress Pathway as a Novel Therapeutic Strategy for Esophageal Squamous Cell Carcinoma

Abstract: Despite recent advances in the management and treatment of esophageal squamous cell carcinoma (ESCC), the prognosis remains extremely poor, and current nonsurgical treatment options are limited. To identify new therapeutic targets, we screened a curated library of epigenetic compounds using a panel of cancer cell lines and found that coinhibiting the histone demethylase LSD1 and the histone methyltransferase G9a potently suppresses cell growth; similar results were obtained by knocking down both LSD1 and G9a e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 55 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…Mechanistically, inhibiting histone methyltransferase eraser LSD1 and writer G9a induces cell death by S-phase arrest and apoptosis, targeting the endoplasmic reticulum (RS) stress pathway, thereby increasing this in-vitro and in-vivo effect. 29 …”
Section: Role and Mechanisms Of G9a In Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, inhibiting histone methyltransferase eraser LSD1 and writer G9a induces cell death by S-phase arrest and apoptosis, targeting the endoplasmic reticulum (RS) stress pathway, thereby increasing this in-vitro and in-vivo effect. 29 …”
Section: Role and Mechanisms Of G9a In Tumorsmentioning
confidence: 99%
“…Mechanistically, inhibiting histone methyltransferase eraser LSD1 and writer G9a induces cell death by S-phase arrest and apoptosis, targeting the endoplasmic reticulum (RS) stress pathway, thereby increasing this in-vitro and in-vivo effect. 29 Hypoxia significantly increases the G9a protein level, which interacts with the Runt domain of RUNX3, increasing its methylation at K129 and K171, promoting cell cycle progression or division, and enhancing the growth of gastric cancer (GC) cells. G9a also inhibits immune responses and cell apoptosis, promoting early tumor growth.…”
Section: Digestive System Tumorsmentioning
confidence: 99%
“…Therefore, inhibiting more than one target simultaneously is a rational strategy. Junxia Min and colleagues found that inactivation of LSD1 with SP2509 and G9a using UNC0642 at the same time markedly suppressed the propagation in ESCC cells through functional screening an epigenetic library in a panel of cancer cell lines [ 12 ]. The authors demonstrated the potent synergistic effect of co-inhibiting LSD1 and G9a in ESCC cells as well as their tumor xenografts [ 12 ].…”
mentioning
confidence: 99%
“…Junxia Min and colleagues found that inactivation of LSD1 with SP2509 and G9a using UNC0642 at the same time markedly suppressed the propagation in ESCC cells through functional screening an epigenetic library in a panel of cancer cell lines [ 12 ]. The authors demonstrated the potent synergistic effect of co-inhibiting LSD1 and G9a in ESCC cells as well as their tumor xenografts [ 12 ]. Additionally, the authors discovered that LSD1 and G9a are both deregulated in ESCC, and patients with high expression levels of both LSD1 and G9a had even significantly poor prognosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation